Characteristics of Female Union Officers in Canada - Chaison, Gary; Andiappan, P. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This study focuses on the characteristics of women who have reached national union office in Canada. Questionnaire responses are analyzed to determine if women are found primarily in un-paid, part-time and union secretary of treasurer positions and to find if less competitive officer positions are occupied by younger, married officers as well as those with children. It was also deter-mined whether female officers tend to run against other females in union elections and come from unions where female members are in the majority.